How winning teams kick for success in Rugby Union: A big data approach - Scott, G. A.; Bezodis, N. E.; Bennett, M.; Church, S.; Waldron, M.; Kilduff, L. P.; Brown, M. R. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Studies within Rugby Union have repeatedly identified kicking as a key indicator of success (1,2), yet no further analysis has been completed to quantify why. While it has been demonstrated that out-kicking your opposition is strategically important, a greater contextual understanding is required to allow deployment of actionable interventions to promote improved outcomes. Given this, the aims of this study were i) to profile the kicks taken during a season of the United Rugby Championship and ii) to quantify whether these kicks differed between winning and losing teams.